Is a patient-specific drill template via a cortical bone trajectory safe in cervical anterior transpedicular insertion? - Peng Peng; Yafei Xu; Xintao Zhang; Meisong Zhu; Bingran Du; Wenrui Li; Wenhua Huang; Jun Song; Jianyi Li (Journal of Orthopaedic Surgery and Research, 2018)
Abstract Background This study aimed to develop patient-specific drill templates by computer numerical control or three-dimensional printing via two cortical bone trajectories (CBTs) and to evaluate their efficacies and accuracies in cervical anterior transpedicular insertion. Methods Preoperative CT images of 20 cadaveric cervical vertebrae (C3–C7) were obtained. After image processing, patient-specific drill templates were randomly assigned to be constructed via two CBTs (CBT0 and CBT0.7) and manufactured by two methods (computer numerical control and three-dimensional printing). Guided by patient-specific drill templates, 3.5-mm-diameter screws were inserted into the pedicles. Postoperative CT scans were performed to evaluate the screw deviation in the entry point and midpoint of the pedicle. The screw positions were also graded. Results Computer numerical control patient-specific drill templates had a significantly shorter manufacturing time compared to three-dimensional-printed patient-specific drill templates (p < 0.01). Absolute deviations at the entry point and midpoint of the pedicle had no significant differences on the transverse and sagittal planes (p > 0.05). There were no significant differences in screw positions (p = 0.3). However, three screw positions were in grade 3 in CBT0, while the others were in grade 1. Conclusions CBT0.7 appears to be a safe and feasible trajectory for cervical anterior transpedicular insertion. Bio-safe computer numerical control patient-specific drill templates can facilitate cervical anterior transpedicular insertion with good feasibility and accuracy.